2018
DOI: 10.3389/fphys.2018.00368
|View full text |Cite
|
Sign up to set email alerts
|

Association Between hMLH1 Promoter Methylation and Risk of Gastric Cancer: A Meta-Analysis

Abstract: Background: Human mutL homolog 1 (hMLH1) is located on chromosome 3q21-23. As a classic tumor suppressor gene, many researchers have studied the association between hMLH1 promoter methylation and gastric cancer, but their conclusions were not always consistent. Therefore, we performed a meta-analysis to make a more integrated and precise estimate of the associations.Method: PubMed, EMBASE, and Cochrane Library were retrieved without language restrictions. Data were analyzed by Review Manager 5.2 and Stata 12.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Mutations in hMSH3 and hMSH6 (DNA MMR gene), receptors of growth factors, and transforming growth factor β-RII are seen in MSI-positive gastric carcinoma [60][61][62]. Other DNA MMR gene, hMLH1, and sometimes hMSH2 expression are completely lost [63][64][65][66][67]. These findings are enough to suggest that H. pylori causes deficient MMR in the gastric mucosal cells, resulting in the development of early stages of gastric carcinoma (Table 1).…”
Section: Mechanisms Of Induction Of Gastric Carcinomamentioning
confidence: 99%
“…Mutations in hMSH3 and hMSH6 (DNA MMR gene), receptors of growth factors, and transforming growth factor β-RII are seen in MSI-positive gastric carcinoma [60][61][62]. Other DNA MMR gene, hMLH1, and sometimes hMSH2 expression are completely lost [63][64][65][66][67]. These findings are enough to suggest that H. pylori causes deficient MMR in the gastric mucosal cells, resulting in the development of early stages of gastric carcinoma (Table 1).…”
Section: Mechanisms Of Induction Of Gastric Carcinomamentioning
confidence: 99%
“…Additionally, MSI tumors alteration status of genes showed common mutations in major histocompatibility complex class I genes, including B2M and HLA-B. To reveal a precise association between human mutL homolog 1 ( hMLH1 ) promoter methylation and gastric cancer, a meta-analysis study was investigated by Ye et al, 2018 [ 34 ]. It was postulated that hMLH1 promoter methylation had significant correlation with not only microsatellite instability, but also with lymph node metastasis and the low expression of hMLH1 protein.…”
Section: Gastric Cancers With Microsatellite Instabilitymentioning
confidence: 99%
“…MSI may be related to either inherited or acquired defects in the MMR system, the latter including somatic mutations, deep deletions, or epigenetic silencing [1,25,26]. A meta-analysis of 39 studies (patients n = 4895) highlighted the role of MutL homolog 1 (MLH1) promoter methylation as a founder genetic event in GEC [27]. In this study, the frequency of MLH1 epigenetic silencing was significantly higher in GEC compared to controls (odds ratio (OR) = 7.94; 95% confidence interval (95%CI) = 4.32-14.58; p < 0.001), being closely related to MSI (OR = 15.33; 95%CI = 9.26-25.36; p < 0.001) [27].…”
Section: Clinicopathologic and Molecular Features Of Mmr-deficient Gamentioning
confidence: 99%
“…A meta-analysis of 39 studies (patients n = 4895) highlighted the role of MutL homolog 1 (MLH1) promoter methylation as a founder genetic event in GEC [27]. In this study, the frequency of MLH1 epigenetic silencing was significantly higher in GEC compared to controls (odds ratio (OR) = 7.94; 95% confidence interval (95%CI) = 4.32-14.58; p < 0.001), being closely related to MSI (OR = 15.33; 95%CI = 9.26-25.36; p < 0.001) [27]. Furthermore, a meta-analysis involving 48 studies (patients n = 18,612) confirmed that patients with MSI-H GEC (n = 1718; 9.2%) had a significantly better prognosis compared to the microsatellite stable (MSS) counterparts (HR 0.69; 95%CI = 0.56-0.86; p < 0.001) [28].…”
Section: Clinicopathologic and Molecular Features Of Mmr-deficient Gamentioning
confidence: 99%